THE MASTERY OF ENGLISH TOURISM TERMS ACHIEVED BY THE THIRD YEAR STUDENTS OF SMKP SANDHY PUTRA MAKASSAR - Helmi Syukur (Elite : English and Literature Journal, 2017)
AbstractThis research aimed at identifying the student’s achievement in mastering English Tourism terms and factors that influence their achievement the of English tourism Terms at STKIP Sandhy putra 1 Makassar. The data collected were multiple choice test and questionnaire. In doing this research, the writer used descriptive quantitative    with total sampling. The subject of  this research consist of the third year students of SMKP Sandhy Putra 1 Makassar who enrolled in academic. The result of the research showed that out from 60 sample of both departments, hotel affairs accomodation got 7,3 scores and categorized as fairly good, while Tourism Plan department got 8,1 scores and they categorized as good. The research concluded that the third grade students of SMKP Sandhy Putra 1 Makassar generally were good in mastering English Tourism Terms. This was supported by the students’ high motivation, supporting facilities and continuity practising and assignment giving by their teacher.AbstrakPenelitian ini bertujuan untuk mengetahui prestasi belajar siswa dalam menguasai istilah dan faktor Pariwisata Inggris yang mempengaruhi prestasi belajar mereka terhadap Syarat Pariwisata Inggris di STKIP Sandhy putra 1 Makassar. Data yang terkumpul adalah tes pilihan berganda dan kuesioner. Dalam melakukan penelitian ini, penulis menggunakan deskriptif kuantitatif dengan total sampling. Subyek penelitian ini terdiri dari siswa kelas tiga SMKP Sandhy Putra 1 Makassar yang terdaftar di bidang akademik. Hasil penelitian menunjukkan bahwa dari 60 sampel dari kedua departemen, akomodasi urusan hotel mendapat nilai 7,3 dan dikategorikan cukup baik, sedangkan Dinas Pariwisata mendapat 8,1 nilai dan dikategorikan baik. Hasil penelitian menyimpulkan bahwa siswa kelas tiga SMKP Sandhy Putra 1 Makassar umumnya ahli dalam menguasai Persyaratan Pariwisata Bahasa Inggris. Hal ini didukung oleh motivasi, fasilitas pendukung dan kesinambungan pengajaran dan pemberian pelajaran oleh guru mereka.